Resolution #15-08: SGA Resolution Responding to Flag Protest on Campus, April 17, 2015 - Student Government Association, (Valdosta State University) (Valdosta State University, 2015)
Student Government Association (Valdosta State University). "Resolution #15-08: SGA Resolution Responding to Flag Protest on Campus, April 17, 2015," April 20, 2015.
1 pdf document. 1 page. 662568 bytes
Keywords: Student government; Flags; Flags--Desecration; Flags--Political aspects; Student protesters; Electronic records